2019
DOI: 10.1292/jvms.18-0631
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of transient receptor potential melastatin 4 channels in the resting membrane potential setting and cholinergic contractile responses in mouse detrusor and ileal smooth muscles

Abstract: Here, we investigated the effects of 9-hydroxyphenanthrene (9-phenanthrol), a potent and selective transient receptor potential melastatin 4 (TRPM4) channel blocker, on the resting membrane potential and cholinergic contractile responses to elucidate the functional role of TRPM4 channels in the contractile activities of mouse detrusor and ileal longitudinal smooth muscles. We observed that, 9-phenanthrol (3–30 µ M) did not significantly inhibit high K + -induced co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Alom et al [82] investigated the involvement of TRPM4 channels in cholinergic contractile responses in detrusor smooth muscle preparations in mice. They found that 9-phenanthrol significantly inhibited carbachol-induced contractions but did not inhibit contractions due to intracellular Ca 2+ release evoked by the drug, suggesting that the inhibitory effect was primarily due to the inhibition of the membrane depolarization process incurred by TRPM4 channels.…”
Section: Trpm4 and Bladder Functionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alom et al [82] investigated the involvement of TRPM4 channels in cholinergic contractile responses in detrusor smooth muscle preparations in mice. They found that 9-phenanthrol significantly inhibited carbachol-induced contractions but did not inhibit contractions due to intracellular Ca 2+ release evoked by the drug, suggesting that the inhibitory effect was primarily due to the inhibition of the membrane depolarization process incurred by TRPM4 channels.…”
Section: Trpm4 and Bladder Functionmentioning
confidence: 99%
“…Based on the positive correlation between the density of TRPM8 channels in the bladder mucosa and voiding frequency in IDO, and the increased TRPM8 expression in bladder pain patients, it was suggested that these channels were involved in the symptomatology and pathophysiology of these disorders [81,82]. TRPM8 channels have also been implicated in the bladder cooling reflex (BCR) in humans [90,91] and animals [92,93].…”
Section: Trpm8 and Bladder Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…TRPV4 regulates detrusor smooth muscles by evoking cholinergic signaling. 40 It has been reported that increase in TRPV4 expression in the bladder may induce bladder hyperactivity. 41 Furthermore, Rahaman et al 42 showed TRPV4-mediated myofibroblast differentiation and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have suggested that TRPM4 could be a potential therapeutic target for detrusor overactivity. In isolated guinea-pig bladder smooth muscle strips, 9-phenanthrol, a selective inhibitor of the TRPM4 channel, reduced spontaneous contractions as well as contractions elicited by carbachol, KCl, and nerve stimulation [58][59][60][61][62]. Kullmann et al [63], investigating the potential role of TRPM4 in detrusor overactivity following spinal cord transection (SCT) in mice, found that TRPM4 was upregulated in the urothelium and detrusor smooth muscle after the lesion.…”
Section: Trpm4mentioning
confidence: 99%